THE EFFECT OF RISK TOLERANCE, ENTREPRENEURIAL MOTIVATION AND FAMILY ENVIRONMENT ON BUSINESS SKILLS OF UMKM IN MEDAN POLONIA DISTRICT - Maulana Syahri, Ananda; Aditi, Bunga; Ayu Setiamy, Arasy (Berajah Journal, 2024)
This research aims to analyze the influence of risk tolerance, entrepreneurial motivation and family environment on MSME business skills. The population in this study was 1049 MSMEs and the sample in this study using the Slovin technique consisted of 91 MSMEs. The analysis technique used is multiple linear regression. The results of the study indicate that risk tolerance has a positive and significant effect on MSME business skills. Entrepreneurial motivation has a positive and significant effect on MSME business skills. Family environment has a positive and insignificant effect on MSME business skills. Simultaneously shows that risk tolerance, entrepreneurial motivation and family environment have a significant effect on MSME business skills in Medan Polonia District.